Physical Wastewater from Assalaya Sugarcane Factory: Reality and Perception - Khair, A. S. E.; Purwanto, P.; Sunoko, H. R.; Elfaig, A. H. I. (Jurnal Pendidikan IPA Indonesia, 2019)
Wastewater physical examination is acknowledged as one of the fundamental parameters for identifying water quality and alleviating the environmental ramifications caused by waste. This study aims to analyze water quality and determine possible consequences on the White Nile River by performing waste analysis generated by Assalaya factory located in Assalaya province, White Nile state, Republic of Sudan. Samples collected included Total Dissolved Solids (TDS), Turbidity, Total Suspended Solids (TSS), Odor, Color, temperature, and conductivity. This study employed questionnaires to recognize community perceptions. Data analysis revealed that the river had been significantly contaminated. The highest recorded concentrations for TDS, Turbidity, TSS, Odor, and Color were 1186 ppm, 28500 NTU, 2333 Mg/l, unacceptable,840 TCU,1830 Ã‚ÂµS/cm and 37.5 Ã¢ÂÂ°C, respectively. These results are not recommended by the international standard for water quality (WHO) approved range. Hence, to avoid the aftermath of the factory wastewater, this study recommends some actions to promote biological treatments. The stakeholders should inevitably follow the environmental water policy and establish the medication near the river. The government should independently administrate this manner. On the other hand, the factory should obey global transformation towards their production schemes such as Eco-friendly, Green-economy, and Sustainability concept in line with social, economic, and ecology sectors.